PELUANG, TANTANGAN DAN STRATEGI PENGEMBANGAN LITERASI DAN SUMBER DAYA MANUSIA EKONOMI SYARIAH DI INDONESIA - Azwar, Azwar (Polytechnic of State Finance STAN, 2023)
This study aims to describe the opportunities, challenges, and strategies in order to develop literacy and Islamic economic human resources in Indonesia. This research is a descriptive-qualitative research with literature study method and SWOT analysis technique. The results of the study show that Indonesia has the opportunity to support literacy, strengthen human resource development and increase research and development in the field of Islamic economics, including: the rise of halal lifestyle campaigns, the active role of the government through existing regulations, the number of Islamic-based mass organizations (Islamic organizations). , the number of universities as research and development centers for halal products, and the rapid development of technology. However, Indonesia also faces various challenges, including: the limited halal education in early and basic education, the absence of technical guidelines on the development of halal products, the available regulations that do not regulate the development and selection of halal services in Indonesia, the quantity and quality of education. Islamic economics study programs in universities are still relatively low, professional certification bodies and certified experts in the field of sharia economics are still limited, and mapping and synergy between parties in sharia economic research and development is not optimal. Several strategic programs that can be carried out include: a national halal literacy program, a certification acceleration program, an acceleration program for curriculum standardization of educational institutions, the creation of a sharia economic data center, and mapping of universities that can specialize in developing certain sharia economic research.